I nostri valori, rivisti La biblioteconomia in un mondo in trasformazione - Gorman, Michael (Studi e saggi, 2018)
I nostri valori, rivisti is the profound reinterpretation, fifteen years after its first edition, of I nostri valori, which highly influenced the discussion on the present and future of libraries and librarians. The suggested professional values are: management skills, service, intellectual freedom, rationality, literacy and learning, equity of access to knowledge and information, privacy, democracy and, compared to the first edition, Michael Gorman adds the superior good. This is therefore an axiology of the library and even more than that, a defence of the library's value, but also a treatise on the library and the librarians advocacy, of a system and a profession which must continually evolve to reaffirm and consolidate their centrality in the social and cultural context.